UPAYA MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN BAHASA INDONESIA MATERI WAWANCARA MELALUI MODEL PROBLEM BASED LEARNING KELAS V UPT SDN SUMURGUNG 1 TUBAN - Mamluatul Fashihah; Wendri Wiratsiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is intended to improve students' academic achievement in learning Indonesian interview material by applying a problem-based learning model or Problem Based Learning (PBL) in grade V students of SDN Sumurgung 1 Tuban. The research method used is Class Action Research (PTK) which is carried out in 2 cycles. Each cycle includes 1) planning, 2) implementation, 3) observation, and 4) reflection. The subject of the study was 18 students of class VT UPT SDN SDN Sumurgung 1 Tuban. Data collection was carried out through learning outcome tests and observations. Observation data shows that most students face obstacles when studying the field of Indonesian study, especially in interview materials that can have an impact on their learning outcomes. The results of the study show that the implementation of the problem-based learning model can improve students' learning outcomes and show positive responses to learning by using the problem-based learning method. This can be observed from the percentage of students in the first and second stages. The percentage of students in the first phase was 55.5% while the percentage of students in the second stage increased to 94.4%. This shows that the implementation of the problem-based learning model can improve learning outcomes and can be applied as one of the other options for learning methods in elementary schools.